A CONSTRUÇÃO DO COTIDIANO DA MULHER ATRAVÉS DA FALA - Mohr, Priscila H.; Padilha, Laura M.; Vitor, Dalva F. A.; Moresco, Marceli P.; Marcewki, Nairana; Santos, Pablo P. S. d.; Zanon, Renan (Salão do Conhecimento, 2013)
Resumo